2013
DOI: 10.1371/journal.pone.0058726
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate Effects on Systemic and Jaw Osteopenias in Ovariectomized Periostin-Deficient Mice

Abstract: Osteoporosis and periodontal disease (PD) are frequently associated in the elderly, both concurring to the loss of jaw alveolar bone and finally of teeth. Bisphosphonates improve alveolar bone loss but have also been associated with osteonecrosis of the jaw (ONJ), particularly using oncological doses of zoledronate. The effects and therapeutic margin of zoledronate on jaw bone therefore remain uncertain. We reappraised the efficacy and safety of Zoledronate (Zol) in ovariectomized (OVX) periostin (Postn)-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Secondly, periostin could have a direct role on osteoclasts as suggested by in vitro studies [35][36][37]; however, to our knowledge this effect has never been demonstrated in vivo. In a previous study, we did not detect an effect of periostin deficiency on osteoclast numbers, surface or markers of bone resorption either in intact or ovariectomized mice [38]. Hence, these findings suggest an involvement of periostin in osteoclastogenesis only when this is triggered by mechanical stress.…”
Section: Discussionmentioning
confidence: 38%
“…Secondly, periostin could have a direct role on osteoclasts as suggested by in vitro studies [35][36][37]; however, to our knowledge this effect has never been demonstrated in vivo. In a previous study, we did not detect an effect of periostin deficiency on osteoclast numbers, surface or markers of bone resorption either in intact or ovariectomized mice [38]. Hence, these findings suggest an involvement of periostin in osteoclastogenesis only when this is triggered by mechanical stress.…”
Section: Discussionmentioning
confidence: 38%
“…The systemic use of SA has been reported in research 46 focusing primarily on its adverse effects, including esophagitis, gastric ulcers, and osteonecrosis of the jaw. These adverse effects are more common in patients who have received high doses for long periods; the use of low doses, especially when the compound is applied topically, has not shown this association 47 …”
Section: Discussionmentioning
confidence: 99%
“…Bonnet et al. (), however, using oncologic doses of ZA in periostin‐deficient mice did not detect any BRONJ. The controversial findings may be in part due to the variation in animal models used to investigate BRONJ.…”
Section: Discussionmentioning
confidence: 99%